2013
DOI: 10.1590/s0100-06832013000400017
|View full text |Cite
|
Sign up to set email alerts
|

Brachiaria sp yield and nutrient contents after nitrogen and sulphur fertilization

Abstract: SUMMARYAmong the production factors, adequate fertilization is an important tool to raise the productivity of pastoral systems and consequently increase the share of Brazil in the supply chain of primary agricultural products at the global level. The objective of this study was to evaluate the interaction of nitrogen and sulfur fertilization in Brachiaria decumbens Stapf. The experiment in pots with Dystrophic Oxisol was evaluated in a completely randomized design with four replications in a 5 x 3 factorial ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…In addition, the implication that both soil types in the study area is demanding fertilizer application for the better forage production. Tis present study was in agreement with the fndings of [42] who noted that as the level of NKP fertilizer increase (0 to 150 to 300 kg/ha) the mean PH of Brachiaria brizantha c.v Marandu was increased from 6.74 to 7.86 to 10.13 cm, respectively at 60 days of harvesting age. But, the current study values of all experimental Brachiaria grass cultivars are higher than these values (74 to 7.86 to 10.13 cm) reported by [42].…”
Section: Plant Heightsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the implication that both soil types in the study area is demanding fertilizer application for the better forage production. Tis present study was in agreement with the fndings of [42] who noted that as the level of NKP fertilizer increase (0 to 150 to 300 kg/ha) the mean PH of Brachiaria brizantha c.v Marandu was increased from 6.74 to 7.86 to 10.13 cm, respectively at 60 days of harvesting age. But, the current study values of all experimental Brachiaria grass cultivars are higher than these values (74 to 7.86 to 10.13 cm) reported by [42].…”
Section: Plant Heightsupporting
confidence: 93%
“…Tis present study was in agreement with the fndings of [42] who noted that as the level of NKP fertilizer increase (0 to 150 to 300 kg/ha) the mean PH of Brachiaria brizantha c.v Marandu was increased from 6.74 to 7.86 to 10.13 cm, respectively at 60 days of harvesting age. But, the current study values of all experimental Brachiaria grass cultivars are higher than these values (74 to 7.86 to 10.13 cm) reported by [42]. Tis diference might be attributed by the genetic variation of grasses, soil type an fertility, rain fall condition, harvesting age, and methods of establishment.…”
Section: Plant Heightsupporting
confidence: 93%
“…Nitrogen is directly related to forage quality (Teixeira et al 2011;Heinrichs et al 2013), since a part in the synthesis of organic compounds that form the plant structure, such as amino sugars, amines, amides, vitamins, pigments, amino acids, proteins, nucleic acids, and molecule chlorophyll (Mengel and Kirkby 2001). N in plants is responsible for the emergence and development of tillers, leaf, and stem size and formation of proteins (Epstein and Bloom 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained in this study agree with those observed by Custódio et al (2005). In contrast, Heinrichs et al (2013) found no significant effects of sulfur fertilization on K or Ca concentrations.…”
Section: Nutritional Status Of Grassmentioning
confidence: 63%
“…Schmidt and Monteiro (2015) reported that the number of tillers Evaluation of sulfur source and dose on the nutritional state and production of piatã forage in Tanzania grass increased sharply with increasing S availability, reaching 120 and 170 % more tillers per pot at the first and second cut, respectively. The effects of sulfur app1lication on the three primary vegetative parameters evaluated (SDM, RDM, and tiller number; Figures 1A, 1B and 1C, respectively) are fundamental for optimizing the productivity of Piatã grass and assuring fast growth of the plants after cuts or grazes (HEINRICHS et al, 2013;SCHMIDT;MONTEIRO, 2015).…”
Section: Forage Productionmentioning
confidence: 99%